Abiraterone acetate in combination with prednisone in the treatment of metastatic hormone-sensitive prostate cancer: clinical evidence and experience. (January 2019) - Purshouse, Karin; Protheroe, Andrew S.
More than a million men worldwide are diagnosed with prostate cancer every year. After androgen deprivation therapy (ADT), chemotherapy has been the only subsequent intervention to improve survival in the metastatic setting but has limitations for patients who may not tolerate its toxicity profile or are not candidates on the basis of comorbidities. Novel anti-androgens such as abiraterone acetate have shown promise for such patients. This review draws on clinical evidence and experience to identify abiraterone as a well-tolerated, effective alternative to docetaxel. In the castration-resistant setting, studies demonstrated a survival benefit over placebo, prompting further trials in the hormone-naïve population. More recently the STAMPEDE and LATITUDE studies suggest abiraterone has comparable survival outcomes to docetaxel in the castration-sensitive setting, with evidence in favour of its quality of life profile. Available comparisons with docetaxel are limited, but those available suggest they have comparable efficacy. However, the significant cost compared with docetaxel is a major barrier in resource-rationed healthcare settings. Overall, abiraterone is an effective alternative to chemotherapy for men with castration-sensitive prostate cancer, but this should be balanced with the significantly greater cost.